KONSEP PERIJINAN BERWAWASAN LINGKUNGAN DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN - Ni Luh Putu Miarmi (University of Udayana, 2014)
The need for a healthy and sustainable environment into hope everyone all the time. The development of rapid development as a result of the fulfillment of the needs of life with varying levels of need have an impact on the use and management of the environment. Based on this paradigm and the use of environmental management is expected to meet the needs of the present without compromising the rights needs of future generations. Governments in the concept of the welfare state law permitted to intervene in an effort to meet the public welfare through licensing instrument is intended as a means of preventing the destruction of the environment.